THE IMPLEMENTATION OF PERFORMANCE ASSESSMENT MODEL ON PENSION FUND BY MODIFIED BALDRIGE ASSESSMENT AS AN ATTEMPT TOWARDS GOOD PENSION FUND GOVERNANCE (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study aims to formulate and implement performance assessment model on Pension Fund by making some modifications on Baldrige Assessment Method that is adjusted to the condition of Pension Fund A in order to realize Good Pension Fund Governance. This study was designed using case study analysis.  The site of the study was done on Pension Fund A. Furtermore, the informants in this study include the elements of employers, the element of supervisory board, the element of Pension Fund administrators, the element of Pension Fund participants both active and passive, as well as the financial services authority as the regulator. The result of this study was a formula of Modified Baldrige Assessment, which includes the parameter of leadership, strategic planning, stakeholders focus, measurement, analysis, and knowledge management, workforce focus, standard operational procedure focus, result, just and fair distribution of welath and power. Performance assessment reveals that the performance of Pension Fund A is excellent. However, there are elements of hegemony and domination by employers, administrators, and the regulator.